A multiwavelength erbium-doped fiber MOPA laser with partial overlapping linear cavities - Tseng, Chih-Lung; Jou, Jau-Ji; Liu, Cheng-Kuang; Jian, Jia-Hung (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, we propose a multiwavelength erbium-doped fiber laser (MW-EDFL). The configuration of the MW-EDFL consists of several linear Fabry–Perot (FP) cavities and a master-oscillation-power-amplifier (MOPA). These linear FP cavities are partially overlapped and include several sections of EDFs, fiber Bragg gratings (FBGs), and a fiber loop mirror (FLM). In our design, a low cost broadband FLM and six narrowband FBGs were used to obtain a stable six-wavelength fiber laser at room temperature. Using a section of EDF as an MOPA near the output end, the output power of the MW-EDFL is promoted. The characteristics of the MW-EDFL were also simulated by the OptiAmplifier software tool. The results of simulations and experiments match each other very well. The optimizing EDF length of the MOPA is about 1.5 m and the MOPA gains are about 4 dB to 7.5 dB. The linewidth, wavelength drift, and power fluctuation of the MW-EDFL are about 450 kHz, 0.05 nm, and 0.4 dB, respectively.
Optica Applicata, Vol. 39, 2009, nr 3, s. 579-585
Keywords: optyka; mutliwavelength laser; erbium-doped fiber (EDF); master-oscillation-power-amplifier (MOPA)